ANALISIS PERAN NOMOR INDUK BERUSAHA (NIB) TERHADAP LEGITIMASI PENDIRIAN DAN PRASYARAT PENDAFTARAN SERTIFIKASI HALAL PRODUK UMKM DI DINAS KOPERASI - Anwa Ihsan Hidayat; Eka Yunita Putri; Bagus Riski Atmaja; Eva Oktaviany; Aenuliya Aenuliya; Ahmad Jaelani (Al Itmamiy Jurnal Hukum Ekonomi Syariah (Muamalah), 2024)
This study aims to investigate the assistance in making a Business Identification Number (NIB) as business legality and as one of the requirements for registering halal certificates for MSME products at DKUKMPP Cirebon City. The method used in this research is qualitative by utilizing an empirical approach, namely the extent to which the implementation is carried out with the data sources obtained. Data collection techniques are through observation, interviews, and documentation. The results showed that DKUKMPP has fulfilled the government program to assist and guide business actors to obtain a Business Identification Number (NIB) and Halal Certificate, which must be owned by business actors as official identification and ensure that the business is registered and has legal legality. DKUKMPP has a program to introduce the Business Identification Number (NIB) and Halal Certificate to the public.